Analisis Pengaruh Good Corporate Governance Terhadap Financial Distress Dimoderasi Kinerja Keuangan - Fernando Prasetya; Yenni Carolina (Jurnal Akuntansi)
The purpose of this study is to analyze and describe the influence of Good Corporate Governance which is proxied by Institutional Ownership, Managerial Ownership, Board of Directors, Board of Commissioners, Independent Commissioners and Audit Committee on Financial Distress with Financial Performance as a moderator. The research population consists of 170 manufacturing companies in 2020-2021 which are listed on the Indonesia Stock Exchange (IDX). The sample research method used was purposive sampling and 46 units of analysis were selected from 23 companies. The data analysis technique used in this study is regression analysis and uses a quantitative approach using IBM SPSS. The results of the hypothesis test show that Institutional Ownership, Managerial Ownership, Independent Commissioners and the Board of Commissioners have no effect on financial distress while the Board of Directors and Audit Committee have an effect on Financial Distress in companies in the manufacturing sector. The independent variables in this study explain 19.40% of financial distress conditions in manufacturing companies where the other 80.60% are influenced by other variables not analyzed in this study. The results of the study show that financial performance does not moderate the influence of Institutional Ownership, Managerial Ownership, Directors, Independent Commissioners and Audit Committees, while the Board of Commissioners shows a moderating effect on financial distress. Keywords: Good Corporate Governance, Financial Distress, Financial Performance